Open‐access platform to synthesize knowledge of ape conservation across sites. Issue 1 (10th November 2020) - Heinicke, Stefanie; Ordaz‐Németh, Isabel; Junker, Jessica; Bachmann, Mona E.; Marrocoli, Sergio; Wessling, Erin G.; Byler, Dirck; Cheyne, Susan M.; Desmond, Jenny; Dowd, Dervla; Fitzgerald, Maegan; Fourrier, Marc; et al.
Abstract: Despite the large body of literature on ape conservation, much of the data needed for evidence‐based conservation decision‐making is still not readily accessible and standardized, rendering cross‐site comparison difficult. To support knowledge synthesis and to complement the IUCN SSC Ape Populations, Environments and Surveys database, we created the A.P.E.S. Wiki (https://apeswiki.eva.mpg.de ), an open‐access platform providing site‐level information on ape conservation status and context. The aim of this Wiki is to provide information and data about geographical ape locations, to curate information on individuals and organizations active in ape research and conservation, and to act as a tool to support collaboration between conservation practitioners, scientists, and other stakeholders. To illustrate the process and benefits of knowledge synthesis, we used the momentum of the update of the conservation action plan for western chimpanzees ( Pan troglodytes verus ) and began with this critically endangered taxon. First, we gathered information on 59 sites in West Africa from scientific publications, reports, and online sources. Information was compiled in a standardized format and can thus be summarized using a web scraping approach. We then asked experts working at those sites to review and complement the information (20 sites have been reviewed to date). We demonstrate the utility of the information available through the Wiki, for example, for studying species distribution. Importantly, as an open‐access platform and based on the well‐known wiki layout, the A.P.E.S. Wiki can contribute to direct and interactive information sharing and promote the efforts invested by the ape research and conservation community. The Section on Great Apes and the Section on Small Apes of the IUCN SSC Primate Specialist Group will guide and support the expansion of the platform to all small and great ape taxa. Similar collaborative efforts can contribute to extending knowledge synthesis to all nonhuman primate species. Abstract : Exemplary page of the A.P.E.S. Wiki, an open‐access platform with site‐level information on ape conservation status and context. Research highlights: We created the A.P.E.S. Wiki (https://apeswiki.eva.mpg.de ), an open‐access platform with site‐level information needed for evidence‐based conservation. We illustrate the process of knowledge synthesis across sites for western chimpanzees.